PENGGUNAAN MATA UANG LOKAL DALAM PERDAGANGAN INDONESIA, MALAYSIA DAN THAILAND - Supadi, Hafsah; Jamaan, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The purpose of this study is to find out the purposes of Indonesia joined the Local Currency Settlement (LCS) agreement and to analyzed the motivation of Indonesia to join together with Malaysia and Thailand. The use of local currency as an alternative to facilitate trade transactions among Indonesia, Malaysia and Thailand by increasing the use of each country's local currency and reducing dependenccy on the US dollar.In this paper, the author used qualitative research, which is done by explaining the case based on facts. Liberalism theory helps to analyze the role of Nation Actor, through International Trade. Another theoretical framework applied in this research are International Cooperation theory and also the concept of National Interests to assisting the author  to find the answers in this case. The techniques used to collect data to study the case in the form of journals, books, an official document, and websites.The results of this study indicate that the agreement Local Currency Settlement (LCS) among Indonesia, Malaysia and Thailand to assist in completing transactions by using each country's local currency and increase trade also investment among these three countries. The development of LCS shows good progress and then it developed into the investment sector. In the period 2015 to 2018 there was an increase in the trade balance between the three countries, while in 2019 there was a decrease in the trade balance due to the fluctuating exchange rate of the US dolar. In addition, the establishment of implementing regulations by Bank Indonesia provides an impetus for Indonesia to continue to increase the use of local currency and expand to the services and investment sectors Keyword(s): bilateral, Indonesia, LCS, local currency, Malaysia, motivation, Thailand